Modern problems of molecular physics : selected reviews from the 7th International Conference "Physics of Liquid Matter: Modern Problems", Kyiv, Ukraine, May 27-31, 2016 /: selected reviews from the 7th International Conference "Physics of Liquid Matter: Modern Problems", Kyiv, Ukraine, May 27-31, 2016. (2018) - Unknown
No abstract available